Heterogeneous catalytic effects on the characteristics of water-soluble and water-insoluble biocrudes in chlorella hydrothermal liquefaction. (1st June 2019) - Xu, Donghai; Guo, Shuwei; Liu, Liang; Lin, Guike; Wu, Zhiqiang; Guo, Yang; Wang, Shuzhong
Highlights: Catalyst addition and time increment reduced the WSB fraction in total biocrude. Pt/C and Ru/C had a synergetic catalytic effect on the WISB yield increment. Pt/C catalytic effect on yield improvement reduced as residence time increased. Pt/C and Ru/C separately led to WSB and WISB with the best element composition. Pt/C could promote the formation of low-boiling-point compounds in the WSB. Abstract: The hydrothermal liquefaction (HTL) of microalgae produces water-soluble biocrude (WSB) and water-insoluble biocrude (WISB) simultaneously. The effects of heterogeneous catalysts (i.e. Pt/C, Ru/C, and Pt/C + Ru/C) on the properties of the two types of biocrudes derived from Chlorella HTL were explored for the first time. The results show that the addition of catalyst (Pt/C, Ru/C, or Pt/C + Ru/C) and/or the increase of residence time (from 10 to 30 min) could decrease the WSB fraction in total biocrude (WSB + WISB) mainly due to the improvement of the WISB yield. The catalytic effects on the WISB yield primarily occurred at the low algae loading (i.e., 1:10 of algae/water) condition, and there was a certain synergetic catalytic effect between Pt/C and Ru/C at this condition. The catalytic effect of Pt/C on the yields of WISB and total biocrude reduced as residence time increased. At the HTL conditions of 350 °C, 0.3 MPa H2, and 1:5 of algae/water for 30 min, Pt/C and Ru/C separately led to WSB and WISB with the highest C (63.57 and 74.16 wt%), H (7.34 and 8.44 wt%) contents and the lowest N (12.19 and 7.06 wt%), O (14.06 and 9.15 wt%) contents, and the highest HHVs (29.73 and 35.60 MJ/kg). The WISB produced with Pt/C mainly consisted of amides, hydrocarbons, organic acids and phenols. Pt/C could promote the cracking of high-molecular-weight compounds in WSB to form more low-boiling-point compounds.